Doe v. Federal Democratic Republic of Ethiopia. (Harvard Law Review, 2018)
The article discusses the U.S. Court of Appeals for the District of Columbia Circuit's ruling in the 2017 case Doe v. Federal Democratic Republic of Ethiopia (Ethiopia) which deals with American foreign relations law, a sovereign immunity doctrine, and the claim that the Ethiopian government hacked into a former Ethiopian citizen's computer in Maryland and monitored his activities using a spyware software program. The U.S. Foreign Sovereign Immunities Act of 1976 is addressed.